2022
DOI: 10.3390/ijerph19169808
|View full text |Cite
|
Sign up to set email alerts
|

Impression Management on Instagram and Unethical Behavior: The Role of Gender and Social Media Fatigue

Abstract: Impression management (IM) concerns can lead to significant psychological consequences, potentially engendering unethical behavior. Therefore, adopting the stressor–strain–outcome framework, this study explores the effects of IM concerns on unethical behavior through wellbeing, and whether IM on social media (i.e., Instagram) triggers fatigue and results in unethical behavior at work. The findings of two empirical studies (n = 480 and n = 299) in different settings (Kuwait and the UK) suggest that women experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Our study found that the effect of public self-awareness between active social network use and green consumption was significant only for individuals with high impression management motivation. As SNS has become a significant venue for self-presentation ( Yang and Liu, 2017 ), previous studies have explored the antecedents and possible consequences of impression management on SNSs (e.g., Lee and Jang, 2019 ; Al-Shatti et al, 2022 ). This study extends the research on impression management in social networks by examining the moderating role of impression management motives in the relationship between public self-awareness motivated by active SNS use and green consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the effect of public self-awareness between active social network use and green consumption was significant only for individuals with high impression management motivation. As SNS has become a significant venue for self-presentation ( Yang and Liu, 2017 ), previous studies have explored the antecedents and possible consequences of impression management on SNSs (e.g., Lee and Jang, 2019 ; Al-Shatti et al, 2022 ). This study extends the research on impression management in social networks by examining the moderating role of impression management motives in the relationship between public self-awareness motivated by active SNS use and green consumption.…”
Section: Discussionmentioning
confidence: 99%
“… 77 , 78 For example, it has been found that more problematic cell phone use is reported by females, 79–82 adolescents 83 and younger adults, 84 , 85 users with basic education, 79 people who spend increasing time on social networks, 81 , 84 and use many applications. 76 In terms of SMF, there are gender differences 85 , 86 which suggest that women tend to experience fatigue more than men. 87 There is also some evidence that there is a stronger effect of social media usefulness and SMF for young people between 28−37 years old compared to the other age groups.…”
Section: Methodsmentioning
confidence: 99%
“…When the effects of user-related elements are considered, mobile apps exert a greater influence on users’ privacy and private information than their abilities to manage them [ 43 , 44 ]. Furthermore, users’ emotional management may become unsteady if their privacy is repeatedly violated [ 55 ]. The SSO paradigm posits that emotional fatigue is more likely to emerge in situations when one experiences a loss of possible resources, an inability to satisfy media demands, or an expectation of threats to the present resources [ 32 ].…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%